Circulating Tumor Dna As a Biomarker for Early Biochemical Recurrence in Prostate Cancer – A Prospective Multicenter Study - Dr. Akshay Deshpande; Dr. Vivek Mahadeo Barekar; Dr Kishor Maroti Tonge (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Early biochemical recurrence (eBCR) after curative intent treatment for localized prostate cancer (PCa) heralds metastatic progression and cancer specific mortality. Conventional clinicopathologic risk models lack sufficient sensitivity for timely intervention. Circulating tumor DNA (ctDNA) offers a minimally invasive window into minimal residual disease, but its clinical value in localized PCa remains uncertain Methods: We conducted a prospective, observational cohort study across five high volume academic centers. Men with biopsy proven, treatment naïve, intermediate or high risk PCa scheduled for radical prostatectomy (RP) or external beam radiotherapy (EBRT) were enrolled between January 2021 and December 2023. Plasma was collected pre treatment and every three months for 24 months. Ultra deep, 152 gene hybrid capture next generation sequencing with unique molecular identifiers (limit of detection 0.1% variant allele fraction [VAF]) profiled ctDNA. The primary endpoint was eBCR, defined as PSA ≥0.2 ng mL⁻¹ (post RP) or PSA nadir + 2 ng mL⁻¹ (post EBRT) within 18 months. Results: Among 628 evaluable participants (median age 66 y; 54% high risk), baseline ctDNA was detected in 223 (35.5%). During a median 26 month follow up, 118 men developed eBCR. Baseline ctDNA positivity independently predicted eBCR (adjusted hazard ratio 3.64, 95% CI 2.23–5.93; p < 0.001). ctDNA detection preceded PSA defined eBCR by a median 5.3 months (IQR 3.7–6.8). Integrating ctDNA with CAPRA S or D’Amico risk groups improved the c index from 0.71 to 0.83 (p < 0.001). In exploratory analyses, emergent TP53 and BRCA2 loss of function mutations conferred the highest recurrence risk. Conclusion: In this multicenter cohort, ultra deep ctDNA profiling identified men destined for early biochemical failure months before PSA rise, outperforming standard risk stratification. Prospective trials evaluating ctDNA guided adjuvant therapy escalation are warranted.